Association between Contraceptive Usage and Maternal Education towards Birth Spacing: Evidence from Pakistan Demographic Health Survey (PDHS) 2017–18 - Mudasar Ali Nadeem; Shoaib Liaqat; Mussarat Hussain; Dr. Falak Sher (Journal of Management Practices, Humanities and Social Sciences, 2023)
Contraception is a birth control method to prevent unwanted pregnancies. Many developing countries have maintained their birth rates in the last quarter despite various family planning options. Pakistan is also struggles to join this race by inculcating vibrant population growth measures. In this context, many social, cultural, and geographical trends have key roles to play in increasing contraceptive prevalence and acceptance trends in Pakistani society. Education has played an important role in the women's autonomy and effective communication with their husbands about the number of children and contraceptive use. The current study was tried to explore the factors associated (regions, place of residence, and wealth index) with contraceptive use and to find out the relationship between mothers’ education and the adoptability of female birth control methods. The secondary data of 13558 ever-married female respondents aged 15–49 years from the Pakistan Demographic and Health Survey (PDHS) 2017–18 was taken for this study. The stratified sampling technique was used in the survey. Bivariate analysis was applied to investigate the relationship between mothers' level of education and contraceptive use. A Chi-square model was used to see the association with other factors. The study results revealed a positive relationship between maternal education and contraceptive use. Results have indicated that the increased education level of mothers is closely associated with contraceptive use. However, more than half of uneducated mothers (62.1%) did not use contraception. By analyzing the results, it is concluded that educated mothers play a vital role in decreasing fertility rates by using different fertility control methods, so education remains the key factor in increasing the prevalence of contraceptive methods. Along with other facilities regarding birth control, there is a dire need to increase the literacy rate. Considering the study results, it is a prerequisite to designing policies and education reforms to promote birth control through education.